WORKSHOP PENGENALAN PROGRAM DESAIN PCB MENGGUNAKAN PROTEUS DI SMK SAFAATUL UMMAH BREBES - Haris Kuspranoto, Abdul (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2024)
This workshop was held to introduce the Proteus program as a PCB (Printed Circuit Board) design and simulation tool to Safaatul Ummah Brebes Vocational School students, with the main aim of increasing their understanding and skills in designing electronic circuits. This activity includes an introductory theoretical session regarding the basics of using Proteus, a demonstration of making PCB designs, and hands-on practice by participants to complete simple projects. The implementation method consists of a combination of lectures, demonstrations, and project-based practice, with assistance by instructors to ensure participants understand each step. The results of the activity showed that most of the participants succeeded in completing a simple PCB design, showing an increase in their technical abilities. Post-activity evaluation also indicated that this workshop provided significant benefits in broadening students' insight into electronic circuit design and motivating them to learn more about electronic technology. With these positive results, it is hoped that similar activities can be carried out on an ongoing basis to support the development of student competencies in the field of electrical engineering.